Menakar Arah Baru Pertahanan Indonesia: Studi Kasus Kemitraan Militer Indonesia–Turki di Bawah Kepemimpinan Presiden Prabowo - Muhammad Nasir (Konstitusi : Jurnal Hukum, Administrasi Publik, dan Ilmu Komunikasi, 2025)
This research evaluates the direction of Indonesia's defense policy under the leadership of President Prabowo Subianto, taking the Indonesia-Turkey strategic partnership as the main case study. Using a qualitative approach with an instrumental case study method, this research analyzes the dynamics of military cooperation that includes key projects such as the development of the Bayraktar drone, involvement in the KAAN fifth-generation fighter jet, and collaborative submarine construction plans. The results show that these partnerships represent a strategy of defense equipment diversification and strengthening the domestic defense industry, and reflect a shift in Indonesia's strategic orientation from dependence on Western countries towards a more balanced partnership with the Global South. The findings confirm that Prabowo's defense policy shows continuity from the previous period, but also brings innovation through a more pragmatic, independent and responsive approach to regional and global security challenges.